Design Of A Circular Express Route With Limited Stops Derived From A Conventional Route For The BRS System - Carpio, Juan (2025)
Urban public transport congestion reduces user quality of life and system efficiency, posing a major challenge for growing cities. This study designs an express route in a Bus Rapid Service (BRS) system using TransCAD macro-simulation. A model based on origin-destination (OD) data reflects current conditions. The proposal introduces a mid-route turn to optimize West-East trips, where demand is higher, and distance is shorter. Simulation results show a 13.98% reduction in West-East travel time and a 20.19% reduction in East-West travel time. Express routes supported by advanced tools can improve operational efficiency and user experience in public transport.